Conceptual Understanding and Perceptions of Pre-Service Science Teachers in the Predict–Observe–Explain (POE) Model: Evidence from a Mixed-Methods Study - Nelly Adjoa Sakyi-Hagan (Integrated Science Education Journal, 2026)
Purpose of the study: This study examined pre-service science teachers’ conceptual understanding and perceptions of the Predict–Observe–Explain (POE) model-based teaching and learning strategy. Specifically, it aimed to determine how the POE strategy enhances conceptual learning of science concepts while gauging the participants’ views towards the use of the approach. Methodology: A convergent parallel mixed-methods design was employed, involving seventy-three first-year pre-service Integrated Science teachers purposively sampled from a teacher education university. Data were collected during a twelve-week intervention using pre- and post-tests and the Cognitive Perceptions of the POE Model-Based Teaching and Learning (CPPOE) questionnaire. Quantitative data were analysed using descriptive statistics and normalised gain analysis, while qualitative data were thematically analysed to capture participants’ perceptions. Main Findings: Findings revealed that the POE model enhanced participants’ conceptual understanding of selected science concepts, with an average normalised gain 〈g〉 of 0.44 indicating moderate conceptual improvement. Qualitative results also demonstrated positive perceptions with participants revealing that the strategy deepened their understanding, reduced confusion, encouraged curiosity, and helped them relate scientific ideas to everyday experiences. Novelty/Originality of this study: This study contributes original mixed-methods evidence of the POE strategy from a Sub-Saharan African context, demonstrating its dual impact on pre-service science teachers’ conceptual learning and their perceptions. These findings underscore the potential of integrating POE into science teacher education curricula to advance inquiry-driven, evidence-based scientific reasoning and student-centred instruction. The findings are limited to a single cohort of first-year pre-service science teachers within one institution.